Study on Operating Characteristics of Hydro Generator with Different Damper Bar Materials - Qiu, Hongbo; Fan, Xiaobin; Liu, Hua; Feng, Jianqin; Yang, Cunxiang (Recent Patents on Engineering, 2018)
Background: Damper bar is an important component to ensure the security and stability operation of generator. Some patents have been proposed in recent years to deal with generator vibration. Based on the damages of damper bars appeared in many hydropower units, the influences of damper bar material on generator operating characteristics are analyzed. Objective: This study aims to find the suitable material for damper bars to improve the reliable operation of generator. Methods: In this research, a 24-MW bulb tubular turbine generator is taken as an example. The two dimensional model is established by using finite element software, and through the comparative analysis of test results and simulation data, the correctness of the model is verified. The analysis and handling of the electromagnetic parameters are based on the finite element method. Results: The brass, copper iron alloy and copper, three kinds of materials are selected to study the effects of damper bar material on the air gap magnetic field and the saturation degree of the pole shoe magnetic density. At the same time, the influences of damper bar material on the generator losses, torques and eddy current are discussed. Conclusion: The application of copper iron alloy material can reduce the saturation degree of the pole shoe magnetic density, pole-to-pole leakage, eddy current and torque ripple of the generator.
Keywords: copper iron alloy